The efficacy of the peace training packagein on verbal, physical and social bullying of students - shole kia; Shahram Vahedi; Davood Tahmaseb zadeh sheghlar3; Rahim Badri Gargari (مجله علوم روانشناختی)
Background: The research focuses on bullying as an aggressive behavior that has created significant risks in both school and society. Considering the nature of peace education, the investigation aims to explore its impact on the components of bullying in elementary school boys. The primary objective of this research is to address a notable research gap that has not been thoroughly explored until now, emphasizing the central issue of the study. Aims: The aim of the current research is to assess the effectiveness of a peace education package on verbal, physical, and social bullying among male students in the second grade of elementary school. Methods: The research employed a semi-experimental design with pre-test and post-test phases, involving an experimental group and a control group. The statistical population consisted of all male students in the second grade of elementary schools in Urmia during the academic year 2022-2023. A total of 60 students were selected using multi-stage cluster sampling, with 30 participants in each of the experimental and control groups. The data collection tool was the questionnaire of the Peer Relationship Scale for Adolescents (Parda, 2000). Following the pre-test, the experimental group underwent a 13-session, 60-minute peace education package based on UNESCO's peace components (1999). Relevant books and articles were utilized for structuring the educational sessions. Data analysis was conducted using the multivariate analysis of covariance (MANCOVA) through SPSS version 27. Results: The results indicated that the level of bullying in all three dimensions (verbal, physical, and social) significantly decreased in the experimental group compared to the control group after the implementation of the peace education intervention, with a significance level of p< 0.001. Conclusion: Given the significant impact of peace education on reducing bullying among students, educational specialists, teachers, and counselors in schools, especially in elementary education, can utilize this form of education to enhance and improve students' bullying behavior.